The Effect of Mild Gestational Diabetes Mellitus Treatment on Adverse Pregnancy Outcomes: A Systemic Review and Meta-Analysis - Behboudi-Gandevani, Samira; Bidhendi-Yarandi, Razieh; Panahi, Mohammad Hossein; Vaismoradi, Mojtaba (Frontiers in Endocrinology, 2021)
Objectives: The aim of this systemic review and meta-analysis was to investigate the effect of mild GDM treatment on adverse pregnancy outcomes. Methods: A comprehensive literature search was conducted on the databases of PubMed, Scopus, and Google Scholar to retrieve studies that compared interventions for the treatment of mild GDM with usual antenatal care. The fixed/random effects models were used for the analysis of heterogeneous and non-heterogeneous results. Publication bias was assessed using the Harbord test. Also, the DerSimonian and Laird, and inverse variance methods were used to calculate the pooled odds ratio of events. The quality assessment of the included studies was performed using the Modified Newcastle–Ottawa Quality Assessment scale and the CONSORT checklist. In addition, the risk of bias was evaluated using the Cochrane Collaboration’s tool for assessing risk of bias. Results: The systematic review and meta-analysis involved ten studies consisting of 3317 pregnant women who received treatment for mild GDM and 4407 untreated counterparts. Accordingly, the treatment of mild GDM significantly reduced the risk of macrosomia (OR = 0.3; 95%CI = 0.3–0.4), large for gestational age (OR = 0.4; 95%CI = 0.3–0.5), shoulder dystocia (OR = 0.3; 95%CI = 0.2–0.6), caesarean-section (OR = 0.8; 95%CI = 0.7–0.9), preeclampsia (OR = 0.4; 95%CI = 0.3–0.6), elevated cord C-peptide (OR = 0.7; 95%CI = 0.6–0.9), and respiratory distress syndrome (OR = 0.7; 95%CI = 0.5–0.9) compared to untreated counterparts. Moreover, the risk of induced labor significantly increased in the treated group compared to the untreated group (OR = 1.3; 95%CI = 1.0–1.6). However, no statistically significant difference was observed between the groups in terms of small for gestational age, hypoglycemia, hyperbilirubinemia, birth trauma, admission to the neonatal intensive care unit, and preterm birth. Sensitivity analysis based on the exclusion of secondary analysis data were all highly consistent with the main data analysis. Conclusion: Treatment of mild GDM reduced the risk of selected important maternal outcomes. Nevertheless, the treatment could not reduce the risk of neonatal metabolic abnormalities or several complications in newborn.